Assessment of the feed additive consisting of Saccharomyces cerevisiae MUCL 39885 (Biosprint®) for cattle for fattening for the renewal of its authorisation (Prosol SPA) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of the authorisation of Saccharomyces cerevisiae MUCL 39885 (Biosprint®) as a feed additive for cattle for fattening (category: zootechnical; functional group: gut flora stabiliser). The applicant provided evidence that the additive currently in the market complies with the conditions of authorisation. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) confirmed that the use of Biosprint® under the current authorised conditions of use remains safe for the target species, the consumers and the environment. Taking into account the nature of the additive, the FEEDAP Panel concludes that the additive should be considered as a potential skin and respiratory sensitiser, and any exposure through skin and respiratory tract is considered a risk. The additive is not a skin/eye irritant. There is no need to assess the efficacy of Biosprint® in the context of the renewal of the authorisation.